NON-CONVICTION BASED ASSET FORFEITURESEBAGAI UPAYA PENGEMBALIAN KERUGIANNEGARA AKIBAT TINDAK PIDANA KORUPSI - Lulu Mufidah, (Fakultas Hukum Universitas Udayana, 2021)
This study aims to find out the concept of non-conviction based asset forfeiture as an effort to restore state losses due to corruption and to find out the formulation of non-conviction based asset forfeiture in accordance with the legal system in Indonesia. This research uses normative juridical research method that is descriptive analysis, namely research sourced from library research with statute approach, and Conceptual Approach. The results of this study showed that when viewed in the formulation of existing norms and spread in the legislation in Indonesia, in fact Indonesia does not adhere to the concept of nonconviction based asset forfeiture applied in parallel with the seizure of assets in personam, but rather placed as an ammunition if the seizure of assets in personam can not be carried out against polluted property in the framework of implementing state losses. Furthermore, the ineffective seizure of assets resulting from corruption in Indonesia is not actually due to the absence of rules regarding asset seizure related to the formulation of non-conviction-based assets, but rather the lack of uniformity or absence of unification, especially related to the law of non-conviction baset assets in Indonesia that is not the same as the seizure of assets in personam. The promulgation of assets should contain the basis of the claim for asset forfeiture in brakes and non-conviction based asset forfeiture mechanisms that can run concurrently with criminal justice in order to applicatively and maximally recover state losses.